Silicon-Nanographite Aerogel-Based Anodes for High Performance Lithium Ion Batteries - Phadatare, Manisha (Sci Rep, 2019)
To increase the energy storage density of lithium-ion batteries, silicon anodes have been explored due to their high capacity. One of the main challenges for silicon anodes are large volume variations during the lithiation processes. Recently, several high-performance schemes have been demonstrated with increased life cycles utilizing nanomaterials such as nanoparticles, nanowires, and thin films. However, a method that allows the large-scale production of silicon anodes remains to be demonstrated. Herein, we address this question by suggesting new scalable nanomaterial-based anodes. Si nanoparticles were grown on nanographite flakes by aerogel fabrication route from Si powder and nanographite mixture using polyvinyl alcohol (PVA). This silicon-nanographite aerogel electrode has stable specific capacity even at high current rates and exhibit good cyclic stability. The specific capacity is 455 mAh g(−1) for 200(th) cycles with a coulombic efficiency of 97% at a current density 100 mA g(−1).